Portugal 2020: Improving energy efficiency of public infrastructures and the municipalities' triple bottom line. (December 2020) - Vaquero, P.; Dias, M. Ferreira; Madaleno, M.
Abstract: On the 27th of February 2015, it was published, in Portugal, the Regulation for Sustainability and Efficient Use of Resources (RESEUR). This is one of the thematic areas created of Portugal 2020, a partnership agreement between Portugal and the European Commission, that regulates the access to European Structural and Investment Funds. RESEUR frames different Investment Priorities (IP) and this research focus on the one that respects energy efficiency, intelligent energy management and the use of renewable energy in local government buildings, street lighting and social housing. We concluded that, despite there were, until now, 87 opportunities for proposal submission, only 46 % of the municipalities have approved projects and no more than 35 % of the budget for this IP is allocated. Until now, € 121 million were approved in this IP, with only 4.2 % meant to interventions in public buildings, although it is the intervention axis with a closer approach to Triple Bottom Line (TBL). Defining a "Decision Triangle" and introducing a political dimension in TBL, we verified that most of the approved projects and the funds allocated refer to social housing and street lighting, i.e. based on the available data there is no demand for TBL balance.